THE ARCHITECTURAL STYLE WHICH ATTRACTS PEOPLE TO THE TRADITIONAL URBAN VILLAGE: KAMPONG BHARU AS A CASE STUDY - Ibrahim, Nur Athirah; Ja’afar, Nor Haslina; Abdul Malek, Mohd Iskandar; Mokhtar, Noor Aisyah (PLANNING MALAYSIA, 2022)
The traditional village is one of the urban design typologies where its survival depends on its success in attracting people. The number of people visiting an area can be considered as one of the factors used in assessing the overall success of a place. However, due to rapid urbanisation, the unique character of traditional villages in urban areas or cities can be seen as outdated or considered as not worth preserving. Thus, this paper aims to identify the buildings within a village that can create a character for the area, and which act as important physical elements that contribute towards the success of a traditional village in an urban setting. This case study was conducted in Kampong Bharu, Kuala Lumpur, and a mixedmethod approach was used involving personal observations, in-depth interviews, and questionnaires with 330 respondents. The result revealed that buildings, as a physical element, play an essential role in attracting people to Kampong Bharu. Thus, this element should be considered for preservation in any regeneration programme targeted at existing traditional villages which are located in urban settings.